The Folkloric Literature in the Teacher’s Classroom: a Way to Recover Tradition through Poetry and the Narration - Bianchi Bustos, Marcelo Emilio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2017)
The literature of folk tradition takes on special importance in the initial education. For that reason we decided to develop a project with the teaching students who were in the initial level so that they understand its importance and that, later on, they were able to apply a series of knowledge and strategies in the classroom. We theorized about the importance of narration and/or reading of diverse narrative and poetic texts of oral tradition of Latin American origin so that they could access the different cultures that today coexist in many of the gardens of Buenos Aires as a product of immigration.